ANALISIS USER EXPERIENCE APLIKASI REGSOSEK PADA BADAN PUSAT STATISTIK INDRAMAYU MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE - Darsanto; Kaiman Maulidani, Mohammad (NUANSA INFORMATIKA, 2023)
The advances of information technology have also brought significant changes to the government in carrying out administrative tasks and communication. In this context, sophisticated information systems enable governments to maximize their efficiency and effectiveness, to reduce costs, and to improve strategic decision-making. The Central Statistics Agency (BPS) carries out Research and Research activities in all provinces in Indonesia. The regsosek application itself is an application that is used to facilitate the collection and processing data related to the socio-economic needs of the community such as employment, health, education, and so on. The focus of this research is to find out the deficiencies or problems that exist in the application by measuring the users’ experience of the research and study application using the User Experience Questionnaire. Data analysis and evaluation are divided into two, namely quantitative data analysis for validity and reliability tests and descriptive statistical analysis using UEQ analysis tools version 11 to determine the average value (mean) of each variable. The results of the quantitative data analysis show that the validity value of the Pearson Product Moment correlation exceeds the value of 0.304 and the Croncbach alpha value of 0.613, thus the tests carried out can be relied upon to accurately and consistently measure user experience. Furthermore, the results of the descriptive statistical analysis show that the value on the clarity aspect has the lowest average value of the six aspects of UEQ, so that the conclusion is that the Regsosek application users do not understand the function and purpose of the application